POLA PENGELUARAN KONSUMEN SELAMA KETIDAKPASTIAN EKONOMI: PENDEKATAN BERBASIS SURVEI - M. Fakhriansyah; K.M. Faisal Reza; Kurnia Ramadhon (Berajah Journal, 2026)
Economic uncertainty triggered by macroeconomic fluctuations, inflation, and global market dynamics has brought significant changes to consumer behavior and spending patterns. This study aims to analyze consumer spending patterns during periods of economic uncertainty using a survey-based approach. The research method used is a quantitative survey with data collection through structured questionnaires distributed to consumers from various socioeconomic backgrounds. The data obtained were analyzed using descriptive and inferential statistical techniques to identify changes in spending priorities, savings tendencies, and shifts in consumption from secondary to primary needs. The results show that economic uncertainty encourages consumers to be more cautious in making financial decisions, with an increased focus on essential spending, a reduction in discretionary spending, and an increased preference for products with long-term utility. In addition, income level and perceptions of economic stability have been shown to significantly influence variations in consumer spending patterns. These findings provide theoretical contributions to understanding the dynamics of consumer behavior in unstable economic conditions and provide practical implications for businesses and policymakers in designing adaptive marketing strategies and economic policies.